Processing method for controlling Al-Mg-Si-Mn phase precipitation and grain structure and application thereof

Through specific processing heat treatment methods, the precipitation of Mn-containing phases in Al-Mg-Si-Mn alloy is regulated to form grain structures of sandwich structures, solving the problem of insufficient strength performance in the prior art, and realizing high-strength 6-series aluminum alloy Application to automotive parts.

CN119433392APending Publication Date: 2025-02-14NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411571208.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the precipitation of Mn-containing phases in Al-Mg-Si-Mn alloys, and it is difficult to obtain sandwich structure grain structure with high strength properties.

Method used

Through specific processing heat treatment methods, including secondary homogenization treatment, rapid cooling, heating and extrusion, the precipitation of Mn-containing phases is regulated to form a uniform and dispersed tissue in the matrix with Mn-containing diffuse phases, and finally obtain a sandwich structure. grain structure.

Benefits of technology

It has achieved the strength performance improvement of high-strength 6-Series aluminum alloy, with tensile strength of 390-440MPa and yield strength of 360-415MPa, and is suitable for automotive anti-collision beams and cross beams.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433392A_ABST
    Figure CN119433392A_ABST
Patent Text Reader

Abstract

The invention discloses a processing method for controlling precipitation of an Al-Mg-Si-Mn-containing phase and a grain structure and application of the processing method, and belongs to the technical field of metal material processing. The processing method comprises the following steps: S1, smelting and casting to obtain an Al-Mg-Si-Mn alloy cast ingot; s2, carrying out secondary homogenization treatment on the cast ingot; s3, after homogenization, quickly transferring to a cooling area; s4, cooling the cast ingot in a cooling area, wherein the cooling is secondary cooling; s5, the cast ingot is heated, and heating is second-stage heating; s6, the heated casting rod is extruded, and the on-line cooling rate of the profile is controlled; and S7, cooling to obtain a profile product. According to the method, a grain structure of a specific sandwich structure is obtained, fiber-state grains are reserved in the structure to the maximum extent, and the strength performance of the 6-series alloy can be improved. The method is wide in application and can be applied to machining of 6110, 6110A, 6013, 6056 and other high-strength 6-series alloy profiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a processing method for controlling the precipitation of Al-Mg-Si-Mn phase containing Mn and grain structure and application thereof, belonging to the technical field of metal material processing. Background Art

[0002] Aluminum alloys have the characteristics of low density, high specific strength, good toughness and corrosion resistance, and are widely used in aviation, aerospace, transportation, machinery, 3C electronics and other fields. Al-Mg-Si-Mn alloys belong to the 6 series alloy category and are heat-treated and strengthened alloys, especially high-strength 6 series alloys, which have broad application prospects in lightweight structural parts for transportation.

[0003] Regarding further improving the strength performance of 6 series alloys, most of the research work focuses on how to increase the number of main strengthening precipitation phases and how to regulate the precipitation of the main strengthening precipitation phases. The research focus of the present invention is how to regulate the precipitation of Mn-containing precipitation phases by processing heat treatment, and the influence on the subsequent processed grain structure morphology to obtain a specific sandwich structure grain structure. This organization retains fibrous grains to the maximum extent, which can further improve the strength performance of 6 series alloys. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a processing method for controlling the precipitation of the Mn-containing phase and the grain structure of the Al-Mg-Si-Mn, aiming to regulate the precipitation of the Mn-containing phase through a suitable processing heat treatment method, and at the same time obtain a specific grain structure of a sandwich structure, thereby further improving the strength performance of the 6 series alloy.

[0005] At the same time, the present invention provides a high-strength 6 series aluminum alloy obtained by adopting a processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure.

[0006] At the same time, the present invention provides an application of a high-strength 6-series aluminum alloy in automobile anti-collision beams and automobile cross beams.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure, comprising the following steps:

[0009] S1. Melting and casting to obtain an Al-Mg-Si-Mn alloy ingot;

[0010] S2. The ingot is subjected to secondary homogenization treatment;

[0011] From room temperature, heat up to 420-480℃ at an average heating rate of 30-350℃ / h or over 1.3-13h, and keep warm for 0-10h; then heat up to 540-575℃ at an average heating rate of 30-400℃ / h or over 0.3-3.2h, and keep warm for 4-30h;

[0012] S3. After the secondary homogenization treatment, it is quickly transferred to the cooling area, and the transfer time is less than 12 minutes;

[0013] S4. The ingot is cooled in a cooling zone, and the cooling is secondary cooling;

[0014] The ingot is cooled in the cooling zone from high temperature to 200°C at an average cooling rate of >200°C / h or over 0.9-1.7h, and then cooled to room temperature at an average cooling rate of 10-200°C / h or over 0.9-17h;

[0015] S5. The ingot is heated, and the heating is secondary heating;

[0016] The ingot is rapidly heated from room temperature to 480-560°C at an average heating rate of 120-600°C / h or over 0.88-3.75h. After reaching the temperature, it is quickly transferred to the holding zone with a transfer time of <2min, a holding temperature of 480-560°C, and a holding time of 0-1h.

[0017] S6. The heated ingot is extruded, and the online cooling rate of the profile is controlled to cool to <200°C at an average cooling rate of >300°C / min or 30-79s;

[0018] S7. After cooling, a profile product with the desired cross section is obtained.

[0019] Preferably, in S1, the Al-Mg-Si-Mn alloy includes any one of 6110, 6110A, 6013, and 6056 alloys.

[0020] Preferably, in S3, the transfer time is less than 10 min.

[0021] Preferably, in S4, the ingot is cooled in the cooling zone from high temperature to 200°C at an average cooling rate of >300°C / h or over 0.9-1.7h, and then cooled to room temperature at an average cooling rate of 10-200°C / h or over 0.85-17h.

[0022] Preferably, in S5, the ingot is rapidly heated from room temperature to 500-540°C at an average heating rate of 120-600°C / h or over 0.78-4.25h. After reaching the temperature, it is rapidly transferred to the insulation zone, the transfer time is <1min, the insulation temperature is 500-540°C, and the insulation time is 0-1h.

[0023] Preferably, in S7, the profile product includes an automobile anti-collision beam or an automobile cross beam.

[0024] Preferably, in S1, the melting and casting adopts a semi-continuous casting method, with a melting temperature of 700-760°C, a casting temperature of 690-730°C, and a casting speed of 40-80 mm / min.

[0025] Preferably, in S6, the extrusion ratio is controlled at 20-60, preferably 30-50, and online cooling is performed while extruding.

[0026] The high-strength 6-series aluminum alloy obtained by the processing method of the present invention has a Mn-containing dispersed phase uniformly and dispersedly distributed in the matrix, an average outer diameter of the Mn-containing dispersed phase is 100-300nm, and the Mn-containing dispersed phase is beneficial to controlling the recrystallization of the profile, and finally obtaining a sandwich structure grain structure.

[0027] The upper and lower surfaces of the sandwich structure are recrystallized grain layers, and the thickness of the upper surface or the lower surface does not exceed 500 microns; the middle is a fibrous grain layer.

[0028] The tensile strength of high-strength 6 series aluminum alloy is 390-440MPa and the yield strength is 360-415MPa.

[0029] The high-strength 6-series aluminum alloy obtained by the present invention is used in automobile anti-collision beams and automobile cross beams.

[0030] The present invention has the following beneficial effects:

[0031] The present invention proposes a processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure, which regulates the precipitation of Mn-containing precipitated phase by appropriate processing heat treatment, and obtains a structure in which a Mn-containing dispersed phase is uniformly and dispersedly distributed in the matrix, which is conducive to controlling the recrystallization of the profile, and finally obtains a specific sandwich structure grain structure. In this structure, fibrous grains are retained to the maximum extent, which can further improve the strength performance of 6 series alloys. The processing method of the present invention is widely used and can be applied to the processing of high-strength 6 series alloy profiles such as 6110, 6110A, 6013, and 6056. It can be widely used in the processing of products such as automotive anti-collision beams and cross beams. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic diagram of a typical sandwich grain structure obtained in Example 1 of the present invention;

[0033] Figure 2 This is a photo of the sandwich structure grain structure of Example 1 of the present invention;

[0034] Figure 3 This is a photo of the internal fibrous tissue of Example 1 of the present invention;

[0035] Figure 4 This is a photograph of the Mn-containing phase precipitation structure in Example 1 of the present invention;

[0036] Figure 5 This is a photo of the sandwich structure grain structure of Comparative Example 1 of the present invention;

[0037] Figure 6 This is a photo of the internal grain structure of Comparative Example 1 of the present invention;

[0038] Figure 7 This is a photograph of the Mn-containing phase precipitation structure of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be further described in detail below in conjunction with specific examples. The following examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0040] Example 1

[0041] The Al-Mg-Si-Mn alloy material provided in this embodiment takes 6110 alloy as an example, and its raw material components are as follows by mass percentage: Mg 1.08wt.%, Si 1.0wt.%, Mn 0.65wt.%, Cu 0.70wt.%, Fe 0.15wt.%, Cr0.20wt.%, Ti 0.02wt.%, and the remainder is Al and unavoidable impurities.

[0042] A processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure, comprising the following steps:

[0043] 1) Raw materials were weighed and smelted according to the mass percentage of each element, and the desired ingot was obtained by semi-continuous casting. The melting temperature was 750° C., the casting temperature was 700° C., and the casting speed was 60 mm / min.

[0044] 2) The ingot is subjected to homogenization treatment, and the temperature is increased from room temperature to 450°C at an average heating rate of 80°C / h or in about 5.3h, and kept at this temperature for 2h, and then the temperature is increased to 570°C at an average heating rate of 50°C / h or in about 2.4h, and kept at this temperature for 10h.

[0045] 3) After the ingot is homogenized, it is quickly transferred to the cooling zone for 9 minutes; then it is cooled to 200°C at an average cooling rate of 300°C / h or after about 1.2 hours, and then cooled to room temperature at an average cooling rate of 50°C / h or after about 3.5 hours.

[0046] 4) The ingot is rapidly heated from room temperature to 520°C at an average heating rate of 350°C / h or over about 1.4h, and then quickly transferred to the holding zone with a transfer time of 40s and kept at 520°C for 30min.

[0047] 5) The heated cast rod is extruded with the extrusion ratio controlled at 40, and cooled to 200°C at an average cooling rate of 400°C / min or in about 50s.

[0048] 6) After cooling, a profile product with the desired cross section is obtained.

[0049] The high-strength 6-series aluminum alloy obtained by the processing method of this embodiment has a uniform and dispersed distribution of Mn-containing dispersed phase in the matrix, and an average outer diameter of the Mn-containing dispersed phase is 100-300nm. The Mn-containing dispersed phase is conducive to controlling the recrystallization of the profile, and finally obtaining a sandwich structure grain structure. The upper and lower surfaces of the sandwich structure are recrystallized grain layers, and the thickness of the upper surface or the lower surface does not exceed 500 microns; the middle is a fibrous grain layer.

[0050] The high-strength 6-series aluminum alloy obtained in this embodiment is used in automobile anti-collision beams and automobile cross beams.

[0051] Example 2

[0052] The Al-Mg-Si-Mn alloy material provided in this embodiment takes 6110 alloy as an example, and its chemical composition is the same as that of Example 1. The difference is that the process used in the ingot cooling stage in the processing method is different, and the ingot is cooled to 200°C in the cooling zone at an average cooling rate of 350°C / h or in about 1.1h after homogenization, and the other processing methods are the same.

[0053] Example 3

[0054] The Al-Mg-Si-Mn alloy material provided in this embodiment takes 6110 alloy as an example, and its chemical composition is the same as that of Example 1. The difference is that the process used in the ingot heating stage in the processing method is different, and the ingot is rapidly heated from room temperature to 520°C at an average heating rate of 400°C / h or in about 1.2h, and the other processing methods are the same.

[0055] Example 4

[0056] The Al-Mg-Si-Mn alloy material provided in this embodiment takes 6110 alloy as an example, and its chemical composition is the same as that of Example 1. The difference is that the process used in the online cooling stage of the profile in the processing method is different, and the profile is cooled to 200° C. at an average cooling rate of 680° C. / min or in about 30 seconds, and the other processing methods are the same.

[0057] In Examples 1 to 4, the heating rate, holding temperature and holding time of the first and second stages during the homogenization process are controlled through a secondary homogenization treatment; the transfer time is effectively controlled through a rapid transfer and a secondary cooling treatment, and the cooling rate of the first and second stages during the cooling process is controlled; the heating rate, heating temperature and holding time of the first and second stages during the heating process are controlled through a secondary heating treatment of the ingot; and the cooling rate of the profile is controlled through an online cooling treatment of the profile.

[0058] The processing heat treatment method of the present invention effectively controls the precipitation morphology of the Mn-containing phase, obtains a uniform and dispersed distribution of the Mn-containing phase, and the Mn-containing phase does not coarsen, with an average outer diameter of 100-300nm. At the same time, the profile obtains a specific sandwich structure, with a completely fibrous structure inside and a recrystallized structure on the surface, and the thickness does not exceed 500 microns.

[0059] like Figure 1 The figure shows a typical sandwich structure schematic diagram of the present invention, where the upper and lower surfaces are recrystallization layers and the middle is a fiber layer.

[0060] like Figure 2 The sandwich grain structure morphology of Example 1 of the present invention is shown, the upper surface or the lower surface is a recrystallized grain morphology, and the thickness does not exceed 500 microns, and the interior is a fibrous grain morphology. Figure 3 This is an enlarged picture of the internal fiber grains.

[0061] like Figure 4 The figure shows the precipitation structure photograph of the Mn-containing phase in Example 1 of the present invention. The Mn-containing phase is uniformly and dispersedly distributed, the phase is not coarsened, and the average outer diameter size is 100-300nm.

[0062] Example 5

[0063] The Al-Mg-Si-Mn alloy material provided in this embodiment takes 6110A alloy as an example, and its raw material components are as follows in mass percentage: Mg 1.05wt.%, Si 1.00wt.%, Mn 0.65wt.%, Cu 0.75wt.%, Fe 0.15wt.%, Cr0.20wt.%, Ti 0.02wt.%, and the remainder is Al and unavoidable impurities.

[0064] A processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure, comprising the following steps:

[0065] 1) Raw materials were weighed and smelted according to the mass percentage of each element, and the desired ingot was obtained by semi-continuous casting. The melting temperature was 700° C., the casting temperature was 690° C., and the casting speed was 40 mm / min.

[0066] 2) The ingot is subjected to homogenization treatment, and the temperature is increased from room temperature to 420°C at an average heating rate of 30°C / h or in about 13 hours, and then increased to 540°C at an average heating rate of 400°C / h or in about 0.3 hours, and kept at this temperature for 4 hours.

[0067] 3) After the ingot is homogenized, it is quickly transferred to the cooling zone for 12 minutes; then it is cooled from 540°C to 200°C at an average cooling rate of 200°C / h or after about 1.7 hours, and then cooled to room temperature at an average cooling rate of 10°C / h or after about 17 hours.

[0068] 4) The ingot is rapidly heated from room temperature to 480°C at an average heating rate of 120°C / h or over about 3.75h, and then rapidly transferred to the holding zone for 2min.

[0069] 5) The heated cast rod is extruded with the extrusion ratio controlled at 30, and cooled from 480°C to 200°C at an average cooling rate of 300°C / min or in about 56s.

[0070] 6) After cooling, the profile product with the required cross section is obtained.

[0071] The high-strength 6-series aluminum alloy obtained by the processing method of this embodiment has a uniform and dispersed distribution of Mn-containing dispersed phase in the matrix, and an average outer diameter of the Mn-containing dispersed phase is 100-300nm. The Mn-containing dispersed phase is conducive to controlling the recrystallization of the profile, and finally obtaining a sandwich structure grain structure. The upper and lower surfaces of the sandwich structure are recrystallized grain layers, and the thickness of the upper surface or the lower surface does not exceed 500 microns; the middle is a fibrous grain layer.

[0072] The high-strength 6-series aluminum alloy obtained in this embodiment is used in automobile anti-collision beams and automobile cross beams.

[0073] Example 6

[0074] The Al-Mg-Si-Mn alloy material provided in this embodiment takes 6013 alloy as an example, and its raw material components are as follows by mass percentage: Mg 1.05wt.%, Si 1.0wt.%, Mn 0.70wt.%, Cu 0.75wt.%, Fe 0.15wt.%, Cr0.10wt.%, Ti 0.02wt.%, and the remainder is Al and unavoidable impurities.

[0075] A processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure, comprising the following steps:

[0076] 1) Raw materials were weighed and smelted according to the mass percentage of each element, and the desired ingot was obtained by semi-continuous casting. The melting temperature was 760° C., the casting temperature was 730° C., and the casting speed was 80 mm / min.

[0077] 2) The ingot is subjected to homogenization treatment, and the temperature is increased from room temperature to 480°C at an average heating rate of 350°C / h or in about 1.3h, and kept at this temperature for 10h, and then the temperature is increased to 575°C at an average heating rate of 30°C / h or in about 3.2h, and kept at this temperature for 30h.

[0078] 3) After the ingot is homogenized, it is quickly transferred to the cooling zone for 10 minutes; then it is cooled from 575°C to 200°C at an average cooling rate of 400°C / h or after about 0.9h, and then cooled to room temperature at an average cooling rate of 200°C / h or after about 0.85h.

[0079] 4) The ingot is rapidly heated from room temperature to 560°C at an average heating rate of 600°C / h or over about 0.88h, and then rapidly transferred to the holding zone for 1min.

[0080] 5) The heated cast rod is extruded with the extrusion ratio controlled at 50, and cooled from 560°C to 100°C at an average cooling rate of 350°C / min or in about 79s.

[0081] 6) After cooling, a profile product with the desired cross section is obtained.

[0082] The high-strength 6-series aluminum alloy obtained by the processing method of this embodiment has a uniform and dispersed distribution of Mn-containing dispersed phase in the matrix, and an average outer diameter of the Mn-containing dispersed phase is 100-300nm. The Mn-containing dispersed phase is conducive to controlling the recrystallization of the profile, and finally obtaining a sandwich structure grain structure. The upper and lower surfaces of the sandwich structure are recrystallized grain layers, and the thickness of the upper surface or the lower surface does not exceed 500 microns; the middle is a fibrous grain layer.

[0083] The high-strength 6-series aluminum alloy obtained in this embodiment is used in automobile anti-collision beams and automobile cross beams.

[0084] Example 7

[0085] The Al-Mg-Si-Mn alloy material provided in this embodiment takes 6056 alloy as an example, and its raw material components are as follows by mass percentage: Mg 1.00wt.%, Si 1.24wt.%, Mn 0.75wt.%, Cu 0.90wt.%, Fe 0.15wt.%, Cr0.20wt.%, Ti 0.02wt.%, and the remainder is Al and unavoidable impurities.

[0086] A processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure, the difference between this embodiment and embodiment 1 is only that:

[0087] The ingot was rapidly heated from room temperature to 500°C at an average heating rate of 600°C / h or over about 0.78h, and then rapidly transferred to the holding zone for 1min.

[0088] In step 5), the extrusion ratio is controlled at 20.

[0089] Example 8

[0090] The difference between this embodiment and embodiment 7 is only that: a processing method for controlling the precipitation of Al-Mg-Si-Mn containing Mn phase and grain structure, the ingot is rapidly heated from room temperature to 540°C at an average heating rate of 120°C / h or for about 0.78h, and then quickly transferred to the holding zone, the transfer time is 0.5min, the holding temperature is 540°C, and the holding time is 1h. In step 5), the extrusion ratio is controlled at 60.

[0091] Comparative Example 1

[0092] The Al-Mg-Si-Mn alloy material provided in this comparative example takes 6110 alloy as an example, and its chemical composition is the same as that of Example 1. The difference is that the process used in the homogenization stage in the processing method is different, the ingot is heated from room temperature to 400°C at an average heating rate of 20°C / h or for about 18.8h, and kept warm for 2h, and then heated to 530°C at an average heating rate of 50°C / h or for about 2.6h, and kept warm for 10h, and the other processing methods are the same.

[0093] Comparative Example 2

[0094] The Al-Mg-Si-Mn alloy material provided in this comparative example takes 6110 alloy as an example, and its chemical composition is the same as that of Example 1. The difference is that the process used in the ingot cooling stage in the processing method is different, and after the ingot is homogenized, it is cooled to 200°C in the cooling zone at an average cooling rate of 120°C / h or for about 3.1h, and then cooled to room temperature at 50°C / h or 3.5h, and the other processing methods are the same.

[0095] Comparative Example 3

[0096] The Al-Mg-Si-Mn alloy material provided in this comparative example takes 6110 alloy as an example, and its chemical composition is the same as that of Example 1. The difference is that the process used in the ingot heating stage in the processing method is different, the ingot is heated from room temperature to 520°C at an average heating rate of 100°C / h or for about 5.0h, and is directly extruded without heat preservation, and the other processing methods are the same.

[0097] Comparative Example 4

[0098] The Al-Mg-Si-Mn alloy material provided in this comparative example takes 6110 alloy as an example, and its chemical composition is the same as that of Example 1. The difference is that the process used in the online cooling stage of the profile in the processing method is different, and the profile is cooled to 200°C at an average cooling rate of 80°C / min or in about 255s, and the other processing methods are the same.

[0099] In Comparative Examples 1 to 4, whether the heating rate is low during the homogenization process, or the cooling rate is low during the cooling process after homogenization, or the heating rate is low during the heating of the cast rod, or the cooling rate of the profile is low, it is not conducive to controlling the precipitation morphology of the Mn-containing phase, resulting in a certain degree of coarsening of the Mn-containing phase, and the average outer diameter reaches 500-1000nm. The ability of this form of Mn-containing phase to inhibit recrystallization is weakened, causing a certain degree of recrystallization of the fiber structure inside the profile. This grain morphology is not conducive to improving the strength of the alloy.

[0100] like Figure 5 The figure shows the grain structure morphology of comparative example 1 of the present invention. The upper surface or the lower surface is a recrystallized grain, but the internal fiber structure is recrystallized, and the recrystallized grain morphology is obvious. Figure 6 In the enlarged photo of the internal structure, it can be seen that obvious recrystallization of the fibrous structure occurs.

[0101] like Figure 7 The figure shows the precipitation structure photograph of the Mn-containing phase in Comparative Example 1 of the present invention. The Mn-containing phase has been coarsened to a certain extent, and the average outer diameter has reached 500-1000 nm.

[0102] Table 1 below is a table of strength data of the embodiments of the present invention and comparative examples.

[0103] The mechanical properties test was carried out according to GB / T 16865-2013 standard.

[0104] Table 1 Strength data

[0105]

[0106]

[0107] The processing method obtained by the present invention can well control the precipitation of the Mn-containing dispersed phase in the Al-Mg-Si-Mn alloy, and the Mn-containing phase is uniformly precipitated in the structure without coarsening, and the average outer diameter size is 100-300nm; and the grain structure morphology of the processed profile can be effectively controlled to form a sandwich structure, that is, the interior is a complete fiber structure and the surface is a recrystallized grain structure, and the thickness of the recrystallized structure does not exceed 500 microns. The processing method of the present invention is widely used and can be applied to the processing of high-strength 6-series alloy profiles such as 6110, 6110A, 6013, and 6056.

[0108] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.

[0109] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.

[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A processing method for controlling the precipitation and grain structure of Al-Mg-Si-Mn containing Mn phase, characterized in that: The following steps are involved: S1. Melting and casting to obtain an Al-Mg-Si-Mn alloy ingot; S2. The ingot is subjected to secondary homogenization treatment; From room temperature, heat up to 420-480℃ at an average heating rate of 30-350℃ / h or over 1.3-13h, and keep warm for 0-10h; then heat up to 540-575℃ at an average heating rate of 30-400℃ / h or over 0.3-3.2h, and keep warm for 4-30h; S3. After the secondary homogenization treatment, it is quickly transferred to the cooling area, and the transfer time is less than 12 minutes; S4. The ingot is cooled in a cooling zone, and the cooling is secondary cooling; The ingot is cooled from high temperature to 200°C in the cooling zone at an average cooling rate of >200°C / h or over 0.9-1.7h, and then cooled to room temperature at an average cooling rate of 10-200°C / h or over 0.9-17h; S5. The ingot is heated, and the heating is secondary heating; The ingot is rapidly heated from room temperature to 480-560°C at an average heating rate of 120-600°C / h or over 0.88-3.75h. After reaching the temperature, it is quickly transferred to the holding zone with a transfer time of <2min, a holding temperature of 480-560°C, and a holding time of 0-1h. S6. The heated ingot is extruded, and the online cooling rate of the profile is controlled to cool to <200°C at an average cooling rate of >300°C / min or 30-79s; S7. After cooling, a profile product with the desired cross section is obtained.

2. The processing method according to claim 1, characterized in that: In S1, the Al-Mg-Si-Mn alloy includes any one of 6110, 6110A, 6013, and 6056 alloys.

3. The processing method according to claim 1, characterized in that: In S3, the transfer time is <10 min.

4. The processing method according to claim 1, characterized in that: In S4, the ingot is cooled in the cooling zone from high temperature to 200°C at an average cooling rate of >300°C / h or over 0.9-1.7h, and then cooled to room temperature at an average cooling rate of 10-200°C / h or over 0.85-17h.

5. The processing method according to claim 1, characterized in that: In S5, the ingot is rapidly heated from room temperature to 500-540°C at an average heating rate of 120-600°C / h or over 0.78-4.25h. After reaching the temperature, it is rapidly transferred to the holding zone with a transfer time of <1min, a holding temperature of 500-540°C, and a holding time of 0-1h.

6. The processing method according to claim 1, characterized in that: In S7, the profile products include automobile anti-collision beams or automobile cross beams.

7. The high-strength 6-series aluminum alloy obtained by the processing method according to any one of claims 1 to 6, characterized in that: In the high-strength 6 series aluminum alloy, the Mn-containing dispersed phase is uniformly and dispersedly distributed in the matrix. The average outer diameter of the Mn-containing dispersed phase is 100-300nm. The Mn-containing dispersed phase is beneficial to controlling the recrystallization of the profile and ultimately obtaining a sandwich structure grain structure.

8. The high-strength 6-series aluminum alloy according to claim 7, characterized in that: The upper and lower surfaces of the sandwich structure are recrystallized grain layers, and the thickness of the upper surface or the lower surface does not exceed 500 microns; the middle is a fibrous grain layer.

9. The high-strength 6-series aluminum alloy according to claim 7, characterized in that: The tensile strength of high-strength 6 series aluminum alloy is 390-440MPa and the yield strength is 360-415MPa.

10. Use of the high-strength 6-series aluminum alloy according to claim 7 in automobile anti-collision beams and automobile cross beams.